Isak Saba, Anders Larsen og Matti Aikio – ein komparasjon av dei samiske skjønnlitterære pionerane i Norge - Zachariassen, Ketil (Nordlit, 2012)
The years from 1906 to 1915 were a pioneer period in Sami fiction literature. In this period Sami authors published in their own language the first poem, the first tale, the first novel and the first collections of poetry. Isak Saba’s poem Sámi Soga Lávlla from 1906 marks the start of this period. The poem was first published in Sagai Muittalægje, a Sami newspaper edited by Anders Larsen, as a part of Saba’s election campaign to the Norwegian parliament. Saba was elected in 1906 and then again three years later by an alliance of the Sami movement and the socialists in East- Finnmark. In 1911, after more than seven years, Sagai Muittalægje was shut down due to economic problems. The year after Anders Larsen published Bæivve-Alggo which is the first novel in the Sami language. In their fiction writing both Saba and Larsen, who were teachers, stressed the Sami’s right to learn to read and write their own language and to develop their own culture and against the existing policy of norwegianisation. But not all of the sami’s supported their aims. Matti Aikio, a sami author who wrote in Norwegian and who got his breakthrough among the Norwegians readers in 1906 with his novel I dyreskind, was most of his life in opposition to Saba and Larsen. How did their attitude towards Sami language and culture find expression in their fiction writings and what can explain the difference between these Sami authors?